Clinical characteristics and prognosis of patients treated as invasive pulmonary aspergillosis outside of severe immunosuppression - Furui Liu; Wenling Chen; Honglei Qi; Yonghong Yang; Ying Yang; Zhaojun Wang; Jinyuan Zhu (Scientific Reports)
Abstract This study aimed to identify clinical characteristics and develop a prognostic model for non-neutropenic patients with invasive pulmonary aspergillosis (IPA). A retrospective analysis of 151 IPA patients was conducted, with patients categorized into survival (n = 117) and death (n = 34) groups. Clinical data, including demographics, laboratory tests, and imaging, were collected. Multivariate Cox regression analysis identified glucocorticoid use (odds ratio [OR] = 30.223, 95% confidence interval [CI]: 2.676–341.306), intensive care unit admission (OR = 0.133, 95% CI: 0.023–0.758), and the arterial oxygen partial pressure/fractional inspired oxygen ratio (OR = 0.994, 95% CI: 0.990–0.999) as significant predictors of 28-day mortality. A prognostic model was developed based on these factors, showing high predictive accuracy (receiver operating characteristic curve area of 0.918). The model’s clinical applicability was validated through calibration curves, bootstrap internal validation, decision curve analysis, and clinical impact curves. Kaplan–Meier analysis further confirmed its utility, indicating a worse prognosis for high-risk patients within 50 days and the highest survival rate at 14 days. This novel model offers valuable insights for predicting survival in non-neutropenic IPA patients.